Minecraft Hour Of Code Game:: an analisis by semiotics operations - Menoncini, Lucia (2023)
The National Basis Common Curricular (BNCC) brought the concepts of Computer Science to Brazilian Basic Education curriculum by Computational Thinking (CT) and, at the same time, indicate connections with CT and Mathematics subject on Primary School. This document either says that math teaching must explore many semiotics representations in this stage, agreeing with Raymond Duval theory. Looking for these facts, this paper searching for establish a different view of CT, because this is a new field and needs new contributions. Basis on this research problem: “Which semiotics operations could be explored on the game Minecraft Hour of Code: Aquatics Voyage?”, it was analyzed the aforementioned game on Semiotics Representations theory of Duval, especially the semiotics operations of treatment and conversion. It was concluding that the game explores as treatment as conversion (in both ways) of representations in natural languages and in figural register, and could be a plugged alternative for teaching math and CT development.